KRISIS SISTEM LEGISLASI INDONESIA MENURUT ETIKA DISKURSUS JURGEN HABERMAS - Indra Lukman Siregar; Mexsasai Indra; Hengki Firmanda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The factual symptoms show that the fluctuating state of public trust and the sub-systemsof social life do not work in balance and harmony with what the public wants because the worldof people's lives is shrinking in the face of power and the power of the money system. Whenthe active participation of the people is removed from the decision-making arena and directlytaken over by the control of power, the people, who are in fact the holders of sovereignty, areonly justified in claiming decisions in the name of democracy. This phenomenon is clearly seenin the legislative process in Indonesia.We can never forget that, in the last 5 (five) years alone, there have been many "injuries"in the minds of the people due to haphazard and annoying legislative processes, for example,the Job Creation Law, the Revised KPK Law, the Revised General Election Law, the Revisionto the Regional Head Election Law, the Law on the Formation of Three New Provinces inPapua, the Revision to the State Financial Policy Law, the Law on Sexual Violence, the Lawon Community Organizations, the revision to the Constitutional Court Law, and many others.Departing from the description of the problem above, this must be radically reformed in orderto avoid the destruction of the Indonesian legislative system. So, it is necessary to conductresearch using a normative approach and analyze it qualitatively. The theoretical frameworkemploys Jurgen Habermas' theory of discourse ethics as an analytical tool for delivering writingon solutions to problems with conclusions that lead to legislation with a foundation in people'slegitimacy.Keyword: Discourse ethics, crisis, system, Indonesian legislation